Warming Yang,Promoting Blood Circulation and Inducing Diuresis in the treatment of diabetic nephropathy:a meta-analysis - WANG Lan; WANG Xiao-qin (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy and safety of ’Warming Yang,Promoting Blood Circulation and Inducing Diuresis’ in the treatment of diabetic nephropathy(DN).Methods The used electronic databases contained foreign databases such as PubMed,EMBASE,Cochrane Library,and Chinese databases such as CNKI,SinoMed,Wanfang Data,CQVIP.The clinical data of "Warming Yang,Promoting Blood Circulation and Inducing Diuresis" in treatment of DN were collected comprehensively.The literature retrieval ended on April 1,2016,and the meta analysis of appropriate literature was processed by RevMan 5.3 software.Results The cases of randomized controlled trials totaled16 and the cases of DN patients totaled 1 107.The results of Meta analysis showed that compared to western medicine control group,the experimental group of integrated traditional Chinese medicine and western medicine,based on "Warming Yang and Benefiting Qi,Promoting Blood Circulation and Inducing Diuresis",perfonned better in the significant efficiency and total efficiency of the treatment of DN(RR=1.97,95%CI 1.50~2.59,Z = 4.86,P<0.01;RR=1.48,95%CI 1.35~1.62,Z=8.58,P<0.01),in the decrease of the serum creatinine(MD=-32.33,95%CI-58.20~-6.47,Z =2.45,P= 0.01),in the increase of high density lipoprotein(MD= 0.16,95%CI 0.09~0.23,Z =4.33,P<0.01),in the decrease of cholesterol,triglyceride,low density lipoprotein(MD=-0.82,95%CI 1.28~-0.36,Z = 3.49,P = 0.0005;MD=-0.40,95%CI-0.53~-0.26,Z=5.95,P<0.01;MD=-0.49,95%CI-0.76~-0.21,Z=3.46,P = 0.000 5),in the decrease of urinary protein(MD=-0.46,95%I-0.61~-0.31,Z=6.01,P<0.01),in the control of fasting blood glucose(MD=-0.34,95%CI-0.57~-0.12,Z = 3.00,P = 0.003),and performed the same in the decrease of the levels of tumor necrosis factor alpha(P= 0.33).Conclusions The current limited evidence suggests that the efficacy and safety of integrated traditional Chinese medicine and western medicine in the treatment of DN is better than the traditional protocols alone.